Digital elevation models, old maps, and cultural heritage—geospatial assets for the digital humanities - Ricker, Britta (Frontiers in Communication, 2025)
A spatial approach to the digital humanities connects tangible geographic sources from the past with clues found in the present-day landscape. Landscapes inspire both regional and national identity, while elevation maps can foster understanding of these landscapes. Digital elevation models (DEM) visualized with effective cartographic design principles can reveal spatial patterns that humans and nature have left in the landscape, and that may otherwise go unnoticed. Different types of DEMs are useful for comparing with old maps, thereby highlighting environmental relationships with cultural heritage. Cartography, the art and science of mapmaking, is riddled with decisions when creating a narrative to communicate cultural heritage. In this example from the Netherlands, I illustrate how this exploratory process can reveal minute spatial patterns that demonstrate years of incredible control over the rivers in the landscape and can serve as artifacts that illuminate examples of cultural heritage. Modifying DEM can lead to valuable digital literacy skills and cartographic communication, while also sparking critical thinking about cultural heritage. This type of precision mapping could be an asset to the digital humanities.